Classification of acute myeloid leukemia - Hwang, Sang Mee (Blood Res, 2020)
The World Health Organization (WHO) Classification of Tumors of Hematopoietic and Lymphoid Tissues was revised in 2017 on the basis of recent high-throughput sequencing and gene expression data on hematologic malignancies. This review explores the current WHO classification of acute myeloid leukemia (AML) and related precursor neoplasms, highlighting the changes made in the current edition and focusing on the diagnosis of AML.